Plano nacional de pós-graduação (PNPG 2011-2020) e suas inter-relações com a pós-graduação em educação física no Brasil - Seron, Juliana Montenegro (2014)
The Brazilian graduate has been supported by documents that guide how this field should be organized and developed. They are constantly modified according to the research, training and marketing requirements that change often. As a general document structures to graduate, specific documents tend to be reworded to meet predetermined general guidelines, although it is not possible to say this always occurs and is always the same way. Hence the research's interest to understand the problem as a general document speaks to a specific graduate one, which led us to develop this dissertation and analyze the interrelationship of the National Graduate Plan (PNPG 2011-2020) with the Area Document 2013, from Area 21 of CAPES, in order to observe the degree of adhesion between them and the consequences of adherence to graduate in Physical Education in Brazil. To this, it was selected two representative documents from graduate: the PNPG 2011-2020, which constitutes National Plan basilar guidance for Brazilian graduate, and the Area Document 2013, guiding the actions for graduate in Area 21 of CAPES, in which physical education is inserted. Based on systematic reading of these documents, we seek to understand the degree of adhesion between them as well as the moves that accession triggers to graduate in Physical Education. The Guidelines of documentary research (MINAYO, 2012) guided the specific procedures of this dissertation, as well as analysis of the interrelationship between documents representing the scenario of post-graduation, as PNPG for Brazilian graduate, and Area Document to Area 21, specifically for physical education in this research case. The study points to the high degree of adhesion between the document area and PNPG 2011-2020, given the predominant focus adjustment to the system that hinders or punishes actions that deviate from standard guiding perspective, as well as the predominance of the post-graduation heteronomous model, based on the interests of outside the university organs, such as the State and the market, which tend to intervene in this space focusing on the meeting of their interests